Emulsification of heavy crude oil in brine and its plugging performance in porous media. (16th March 2018) - Yu, Long; Dong, Mingzhe; Ding, Boxin; Yuan, Yanguang
Highlights: Stability, droplet size distribution, and rheological property of heavy oil-in-water emulsion were characterized. Plugging performances of selected emulsions in porous media was tested and analyzed. Effects of oil quality, permeability, droplet size, and flow rate on emulsion plugging were analyzed. Abstract: In this paper, heavy crude oil and formation brine collected from Xinjiang oilfield were used to prepare crude oil-in-water (O/W) emulsions. Emulsification tests were first conducted to screen suitable emulsifiers. Then stability test, droplet size distribution analysis, and rheological property measurements were carried out to investigate the physicochemical characteristics of the developed O/W emulsions. It was found that surfactants of Span 60 and Tween 80 combined with sodium hydroxide could reduce the oil/water interfacial tension and thereby emulsify the heavy crude oil in formation brine. A series of sandpack flow tests were conducted to evaluate the plugging performance of the heavy O/W emulsions, emulsified using 0.1 wt% Span 60–0.1 wt% Tween 80–0.025 wt% NaOH. The flow test results showed that heavy O/W emulsion can result in more than 99% permeability reductions in sandpacks. The permeability reduction by emulsion plugging increased greatly with an increase in oil quality and injected emulsion slug, but decreased with an increase in sandpack permeability and injection flow rate.